Drug Management On Availability Of Drugs In Pharmaceutical Installations Pabatu General Hospital Pt Pmn Using Fifo & Fefo Methods - Fitri Aidani Ulfa Harahap; Ratih Nur Indah Siregar; Widya Yanti Sihotang; Ali Napiah Nasution (International Journal of Health and Pharmaceutical (IJHP), 2022)
Drug management on drug availability at the Pharmacy Installation of Pabatu General Hospital PT PMN Serdang Bedagai is still not good. Drug management includes drug selection, drug planning, and procurement as well as drug storage and distribution. This study aims to determine the management of drug availability at the Pharmacy Installation of Pabatu General Hospital PT PMN Serdang Bedagai. This type of research is a descriptive approach with NLP (Neuro-Linguistic Programming) techniques. The population in this study were all staff or employees at the pharmaceutical installation of Pabatu General Hospital PT PMN Serdang Bedagai and a sample of 9 people. The collection of data with primary and secondary data and the data were analyzed by data reduction, data display (data display), and drawing conclusions or levers. The results showed that the drug management at the Pharmacy Installation of Pabatu RSU PT PMN was effective and efficient which includedinput, process, and output. It is suggested that every human resource in the pharmaceutical installation of Pabatu General Hospital PT PMN should be given the opportunity to improve their knowledge and skills regarding drugmanagement in the installation, so that in the future drug management can be better and the pharmacy installation plays a role in staff development and educational programs such as developing new staff orientation programs, education, and training based on the need for competency development of human resources and head of evaluation to conduct independent research or contribute to research on the development of pharmaceutical service practices in hospitals.